Oxford ion-trap quantum computing project. - Lucas, D; Donald, C; Home, J; McDonnell, M; Ramos, A; Stacey, D; Stacey, J; Steane, A; Webster, S (2003)
We describe recent progress in the development of an ion-trap quantum information processor. We discuss the choice of ion species and describe recent experiments on read-out for a ground-state qubit and photoionization trap loading.